Problematika Kompetensi Guru dalam Menghadapi Tuntutan Pendidikan Abad-21 Era Disrupsi - Pibina, Rahma; Qumairah, Agna; Aulia, Amel; Abdurrahmansyah, Abdurrahmansyah (ALACRITY : Journal of Education, 2025)
The rapid advancement of technology and information in the 21st century has caused major changes in many aspects of life, including the world of education. During this period of disability, transformative innovation requires agile and effective adaptation from all elements of the education system, especially teachers. As the foreground of education, teachers play a vital role in preparing young people to face the challenges and use the possibilities of the disability era. He not only learns teaching materials, he also has the ability to meet the requirements of the 21st century. These 21st century abilities include the ability to critically, creatively, collaboratively, communicatively and critically consider digital capabilities. These abilities are essential for students to adapt to rapid changes, innovate and contribute productively to the global society.  This study seeks to analyze teacher disability in the development of skills related to the requirements of the 21st century in the age of disability. The knowledge from this study is expected to contribute significantly to the development of teacher professionalism, improving the quality of education, and preparing young people who are competitive and competitive on the global stage. It is also expected that this study will include comprehensive and applicable recommendations for stakeholders in the field of education, including the government, educational institutions, and professional organizations, to develop effective and relevant guidelines and programs for professional development for teachers with 21st century needs. To achieve this goal, this study uses a qualitative approach in the literature research method. Literature research is an effort to find research data or information by reading scientific journals, reference works, and published materials available in the library. Data collected from various sources are analyzed using the distance model and Hooverman, including data reduction, data presentation, and drawing conclusions. This study focuses on the analysis of articles, papers, and journals that specifically discuss the challenges of shaping the 21st century in the era of disability, where the subject of teacher competence is experiencing disability. The findings of this study say that educators have a deeper understanding of the challenges of adapting to the dynamics of change in the world of education when adapting. It is also expected that this study will be able to achieve teacher professional development and improve the quality of education in Indonesia.